2021
DOI: 10.31234/osf.io/ux3fc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Truth by Repetition … without repetition: Testing the effect of instructed repetition on truth judgments

Abstract: Past research indicates that people judge repeated statements as more true than new ones. An experiential consequence of repetition that may underly this “truth effect” is processing fluency: processing statements feels easier following their repetition. Here, we examine the effect of merely instructed (i.e., not experienced) repetition on truth judgments, which we compared to the effect of factual repetition. In two preregistered experiments (N=468), we found a larger truth effect for factual repetition compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…An approach-avoidance effect (i.e., an increase in liking for physically-approached relative to physically avoided stimuli) is found when participants are merely instructed of the approached versus the avoided status of the stimuli (Van Dessel et al, 2015). An illusory truth effect (i.e., an increase in the perceived truth for repeated relative to new trivia statements) is found based on the mere instruction that statements are repeated rather than new (Mattavelli et al, in press).…”
Section: An Application Of the Conceptual Model To Evaluative Conditi...mentioning
confidence: 99%
“…An approach-avoidance effect (i.e., an increase in liking for physically-approached relative to physically avoided stimuli) is found when participants are merely instructed of the approached versus the avoided status of the stimuli (Van Dessel et al, 2015). An illusory truth effect (i.e., an increase in the perceived truth for repeated relative to new trivia statements) is found based on the mere instruction that statements are repeated rather than new (Mattavelli et al, in press).…”
Section: An Application Of the Conceptual Model To Evaluative Conditi...mentioning
confidence: 99%
“…One hundred (59 females, 40 males, 1 non-specified, Mage = 37.39, SDage = 5.24) participants were recruited via Prolific Academic and paid for their participation. Five screening criteria were applied: participants were English speakers, declaring to live in the United States, with an approval rate of at least 95%, with at least 100 previous submissions on Prolific, and not having taken part in previous related studies (Studies 1-3 from Mattavelli et al, 2023). The experiment was programmed in Inquisit6.…”
Section: Methodsmentioning
confidence: 99%
“…Repetition influences truth judgments even when participants are told, in the exposure phase, that the information is false (Begg et al, 1992;Skurnik et al, 2005;Unkelbach & Stahl, 2009; see also Henkel & Mattson, 2011); in the face of advice from reliable sources (Unkelbach & Greifeneder, 2018); after long delays (up to months, Brown & Nix, 1996); when explicit indications that statements come from untrustworthy sources are provided (Henkel & Mattson, 2011); and despite monetary incentives (Speckmann and Unkelbach, 2021; see also Brashier & Rand, 2021). Even though recent studies have shown that people underestimate the impact of repetition on their truth judgments (Mattavelli et al, 2023), the reviewed evidence suggests that escaping from the effect of repetition is no trivial task. Remarkably, neither high intelligence nor analytical skills are protective against it (De keersmaecker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%